2011
DOI: 10.1103/physrevb.84.075115
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled cyclic oligothiophene nanotubes: Electronic properties from a dispersion-corrected hybrid functional

Abstract: The band structure and size scaling of electronic properties in self-assembled cyclic oligothiophene nanotubes are investigated using density functional theory. In these unique tubular aggregates, the π -π stacking interactions between adjacent monomers provide pathways for charge transport and energy migration along the periodic one-dimensional nanostructure. In order to simultaneously describe both the π -π stacking interactions and the global electronic band structure of these nanotubes, we utilize a disper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 92 publications
(134 reference statements)
1
36
0
Order By: Relevance
“…Although this is a semiempirical dispersion potential, it has been shown that the DFT-D approach describes well the stacking interactions in π -conjugated organic molecular crystals. 26,27 Structure relaxations with a Monkhorst-Pack sampling k-mesh of 1 × 1 × 5 and 1 × 9 × 5 for the isolated chain and the π -stacked structure, respectively, were performed until the forces on each atom were less than 0.013 eV/Å. The imaginary part of the dielectric function was calculated according to the following equations: 28…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…Although this is a semiempirical dispersion potential, it has been shown that the DFT-D approach describes well the stacking interactions in π -conjugated organic molecular crystals. 26,27 Structure relaxations with a Monkhorst-Pack sampling k-mesh of 1 × 1 × 5 and 1 × 9 × 5 for the isolated chain and the π -stacked structure, respectively, were performed until the forces on each atom were less than 0.013 eV/Å. The imaginary part of the dielectric function was calculated according to the following equations: 28…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…It should also be noted that there are differences between our DFT data and data from other groups, as well as between DFT and experiments. Our DFT calculations use the DFT-D method 48,49 as it gives more accurate cohesive energies and bulk moduli for the CdZnTe compounds. We point out that, for the BOP potential, the relation between bond energy and bond length for the nearest neighbor structures always satisfies Eq.…”
Section: A Small-cluster Propertiesmentioning
confidence: 99%
“…In this paper, the sharp nonlinear forcedisplacement relation is reported at even small displacement via a molecular mechanics model, when the tightly helical carbon tubes (CNTs) (see Fig. [4][5][6][7][8][9] Hayashida et al 10 revealed that the electrical conductivity of the CNCs ranges from 107 to 180 s cm À1 . Helical CNTs (or so-called carbon nanocoils (CNCs)) have been synthesized and studied.…”
Section: Introductionmentioning
confidence: 81%